Personajes colectivos e individuales en Los ríos profundos de José María Arguedas - Huamán, Carlos (2020)
In Los ríos profundos (Deep Rivers), novel by Peruvian José María Arguedas, there is a unique configuration of the characters linked to the Quechua-Andean cultural universe. Thus, both the central and secondary characters tend to become spokesmen for collectives or individuals that, depending on the case, become mythical-symbolic representations.